2010
DOI: 10.3346/jkms.2010.25.11.1652
|View full text |Cite
|
Sign up to set email alerts
|

Time Dependent Bladder Apoptosis Induced by Acute Bladder Outlet Obstruction and Subsequent Emptying is Associated with Decreased MnSOD Expression and Bcl-2/Bax Ratio

Abstract: Ischemia/reperfusion (I/R) injury-induced oxidative stress plays an important role in the functional impairment of the bladder following acute bladder outlet obstruction (BOO) via induction of apoptosis. The purpose of this study was to investigate the time course of the bladder apoptosis, and apoptosis related molecular changes in the early stage of acute BOO. Twelve-week-old male Sprague Dawley rats were divided into control, acute BOO only (I), and acute BOO plus subsequent emptying (I/R) for 30, 60, 120 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 27 publications
0
12
0
1
Order By: Relevance
“…This dose was selected because it has been previously demonstrated that pretreatment with a 30 mg/kg dose of 3-AB before I/R injury exerts protective effects and is well-tolerated with no side effects being observed even when this dose was used long-term in rodents [16,17]. In previous experiment, we found that bladder apoptosis and PARP activity reached a peak at 2 h during various periods of reperfusion for 30 min, 1 h, 2 h, 3 days, 1 week and 2 week [15]. After emptying the bladder, the rats were sacrificed and the bladders were extirpated.…”
Section: Animal Modelmentioning
confidence: 89%
See 1 more Smart Citation
“…This dose was selected because it has been previously demonstrated that pretreatment with a 30 mg/kg dose of 3-AB before I/R injury exerts protective effects and is well-tolerated with no side effects being observed even when this dose was used long-term in rodents [16,17]. In previous experiment, we found that bladder apoptosis and PARP activity reached a peak at 2 h during various periods of reperfusion for 30 min, 1 h, 2 h, 3 days, 1 week and 2 week [15]. After emptying the bladder, the rats were sacrificed and the bladders were extirpated.…”
Section: Animal Modelmentioning
confidence: 89%
“…Recent studies have demonstrated that an increase in PARP activity causes damage of several organs under I/R conditions such as ones seen in brain, kidney, and heart that is significantly attenuated by PARP inhibition [12][13][14]. Previously, a study in our laboratory showed that bladder apoptosis induced by AUR and subsequent bladder emptying is associated with increased PARP activity [15]. The aims of this study were to investigate whether inhibition of PARP could suppress bladder apoptosis following AUR and subsequent bladder emptying, and to explore the possible underlying mechanisms.…”
Section: Introductionmentioning
confidence: 95%
“…26, 27 Previous investigators utilized single bladder distensions as a model of acute urinary retention, but no reports of chronic distension models are known. Following a single bladder distension, a burst in ROS has been documented in conjunction with an increase in pro-apoptotic gene transcription.…”
Section: Discussionmentioning
confidence: 99%
“…The progressive intramural ischemia will eventually lead to nerve damage, creating a vicious circle of worsening sensation and contractility. Even if the overdistension is temporary, the resulting ischemia and subsequent reperfusion are detrimental to the bladder by increasing apoptosis and oxidative damage 11, 12. Nerve and muscle damage from ischemia may cause further bladder function impairment and bladder overdistension, eventually leading to new episodes of AUR, although there is no evidence for this in humans.…”
Section: Pathophysiology and Consequencesmentioning
confidence: 99%